2016
DOI: 10.1371/journal.pone.0167835
|View full text |Cite
|
Sign up to set email alerts
|

Routine Vaccination Coverage in Northern Nigeria: Results from 40 District-Level Cluster Surveys, 2014-2015

Abstract: BackgroundDespite recent success towards controlling poliovirus transmission, Nigeria has struggled to achieve uniformly high routine vaccination coverage. A lack of reliable vaccination coverage data at the operational level makes it challenging to target program improvement. To reliably estimate vaccination coverage, we conducted district-level vaccine coverage surveys using a pre-existing infrastructure of polio technical staff in northern Nigeria.MethodsHousehold-level cluster surveys were conducted in 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 7 publications
(7 reference statements)
1
42
0
Order By: Relevance
“…The low OPV3 coverage among children aged 12–23 months in the 2016–2017 national vaccination survey reflects persistently poor delivery of routine immunization services, particularly in states in northeast and northwest Nigeria ( 10 ). A National Emergency Routine Immunization Coordinating Center has been commissioned to identify and implement strategies to increase vaccination coverage, starting in the poorest performing states.…”
Section: Discussionmentioning
confidence: 99%
“…The low OPV3 coverage among children aged 12–23 months in the 2016–2017 national vaccination survey reflects persistently poor delivery of routine immunization services, particularly in states in northeast and northwest Nigeria ( 10 ). A National Emergency Routine Immunization Coordinating Center has been commissioned to identify and implement strategies to increase vaccination coverage, starting in the poorest performing states.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported factors related to maternal knowledge for instance, knowledge on child immunization [27], knowledge on preventive objective of immunization [24], knowledge on vaccines [57], knowledge on child vaccination schedule which was reported in three studies [29,53,59]. Likewise, awareness on immunization and immunization program was also revealed in three studies [20,32,56].…”
Section: Modi Able Factorsmentioning
confidence: 91%
“…In Burkina Faso, mothers with knowledge on preventive objectives of immunization were more likely to have their children compare with mothers without the knowledge [24]. In a household-level cluster survey consisting of 7,815 children, conducted in Nigeria that involved 40 polio high risk districts of Nigeria, lack of maternal knowledge about vaccines was found to be the highest reasons contributing to poor childhood immunization uptake which accounted for 50% reasons for non-vaccination [57].…”
Section: Maternal Knowledgementioning
confidence: 96%
See 2 more Smart Citations